The Intensity of Social Media Use on Academic Procrastination Behavior - Yuhani Mustika Dewy; Sudarmono Sudarmono; Apuanor Apuanor (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The intensity of social media use on academic procrastination behavior.This study aims to determine the effect of social media usage intensity on academic procrastination behavior among students of the Economics Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Sampit. A qualitative approach with descriptive methods was used in this study, involving three students as subjects representing the categories of low, medium, and high intensity of social media usage. Data were obtained through semi-structured interviews supported by documentation, then analyzed through data reduction, data presentation, triangulation, and the assistance of NVivo 12 software. The results showed differences in the intensity of social media usage in each subject based on aspects of attention, appreciation, duration, and frequency of social media use. Academic procrastination behavior was found in all research subjects, but the role of social media in the emergence of this behavior differed in each category of usage intensity. The higher the intensity of social media usage, the more dominant the role of social media in various forms of academic procrastination shown by students.